Close relationships and diabetes management across the lifespan: The good, the bad, and autonomy. (February 2021) - Kelly, Caitlin S; Berg, Cynthia A
Relationships are linked with positive and negative self-management and illness outcomes for individuals with type 1 diabetes. Explanations for these mixed associations have remained separated in psychosocial research in type 1 diabetes by relationship type (e.g. parent vs spouse) and individual's age (e.g. adolescence vs older adulthood). In this conceptual review, we present a novel perspective that close relationships across the lifespan may be beneficial for illness self-management when they support individuals' sense of autonomy, defined from a Basic Psychological Needs perspective. Processes of autonomy support are crucial for promoting illness management across all ages and relationship types.